Biomedical Optics and 3-D Imaging 2010
DOI: 10.1364/biomed.2010.bwa7
|View full text |Cite
|
Sign up to set email alerts
|

Laser Speckle Imaging in the Spatial Frequency Domain

Abstract: Laser Speckle Imaging (LSI) images interference patterns produced by coherent addition of scattered laser light to map subsurface tissue perfusion. However, the effect of longer path length photons is typically unknown and poses a limitation towards absolute quantification. In this work, LSI is integrated with spatial frequency domain imaging (SFDI) to suppress multiple scattering and absorption effects. First, depth sensitive speckle contrast is shown in phantoms by separating a deep source (4 mm) from a shal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…This decrease in contrast with an increase in μ Likewise, in this study, contrast decreased linearly as absorption increased. Others 8,9 have reported an increase in contrast as absorption increases. At initial glance, it may appear that these results are contradictory.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This decrease in contrast with an increase in μ Likewise, in this study, contrast decreased linearly as absorption increased. Others 8,9 have reported an increase in contrast as absorption increases. At initial glance, it may appear that these results are contradictory.…”
Section: Discussionmentioning
confidence: 89%
“…The confounding effect of changes in absorption was not considered in Khaksari and Kirkpatrick. 5 Changes in observed speckle contrast in LSCI due to changes in hematocrit 8 or directly due to changes in μ s and μ a in phantom materials have been described by others in the literature; 9 however, a systematic study of the combined effects of absorption and scattering on the observed contrast values in LSCI has yet to be reported.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In another study [41], the authors have used a transmission geometry through the finger joint, 1.0-1.5 cm, but did not use a proper physical model or achieved any depth resolution. Depth sensitive speckle contrast measurement using a sinusoidally modulated source is used in [42], where a pair of confined flows separated 2 mm apart and at a depth of 2 mm and 4 mm were measured. Although this work presents the relation connecting speckle contrast to the electric field autocorrelation for sinusoidal source excitation, a quantitative recovery of the effective flow velocity from the measured speckle contrast was not presented.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effects of sample mechanics, the evolution of the g 2 (t) curve is also influenced in part by factors such as the optical properties of blood (Eq. (2) and speckle contrast [19,43,44]. We have previously demonstrated that an increase in optical scattering can accelerate the decay rate of the measured g 2 (t) curve independent of sample mechanical properties due to an increase in the number of scattering events per optical path [19].…”
Section: Discussionmentioning
confidence: 92%